Impact of physical and sports rehabilitation on the level of physical fitness of combatants - Nataliia Krushynska; Iryna Kohut; Ievgen Goncharenko (Kharkiv State Academy of Physical Culture, 2023)
The anti-terrorist operation, the operation of the joint forces, and the full-scale war in Ukraine have a significant physical and psychological impact on the participants of the hostilities. One of the negative consequences of war is the loss of physical health which further affects the process of socialization during a peaceful life. At the same time, the process of restoring physical health with the help of physical culture and sports rehabilitation has not been researched enough, which confirms the relevance of the chosen topic. Objective: to determine the impact of physical culture and sports rehabilitation on the level of physical fitness of combatants. Material and methods: the research was carried out on the basis of the National Sports Complex "Olympiyskyi" in the group "Veteran Ten" during 2020-2021. The main sports competitions the combatants were preparing for were various marathons. 40 combatants who had completed their military service took part in the research. During the research, there were used the following methods: pedagogical experiment, and methods of mathematical statistics. Results: During a year, combatants participated in the research in the framework of which they trained and prepared to participate in mass races. The content of the training included both running exercises and exercises aimed at developing strength qualities (mainly strength endurance), flexibility, and coordination. The level of physical fitness of combatants was tested in dynamics (before the start of training and after a year of training). The level of physical fitness of combatants was determined according to the approved tests and standards of the "Annual Assessment of Physical Fitness of the Population of Ukraine". Based on the results of the research, it was established that at the initial stage, 75% of the combatants had a low level of physical fitness, 23% had a medium level, and 2% had a sufficient level. Upon the completion of the pedagogical experiment, the level of physical fitness of the combatants improved: 33% of the combatants had a low level of physical fitness, 50% had a medium level, and 17% had a sufficient level, which demonstrates the effectiveness of training sessions as a means of physical culture and sports rehabilitation. Conclusions. The positive impact of physical culture and sports rehabilitation on the level of physical fitness of combatants was determined. With the help of the tests and standards of the "Annual Assessment of Physical Fitness of the Population of Ukraine", it was discovered that the indicators of physical fitness of the combatants at the first stage of the research were in the range from 2 to 21 and on average were (11.83; 4.49) points. In the second stage, they ranged from 11 to 24, their average physical fitness score was (11.28; 3.20) points. At the same time, 46.1% of the participants of the research got an observed increase in the indicator which turned out to be statistically significant (t=13.563; df=39; p<0.05). Therefore, it can be stated that running sessions have a positive impact on the level of physical fitness of combatants.